India's States: The Struggle to Govern. (June 2016) - Manor, James
This article analyzes recent variations in governing strategies in different Indian states. Those variations mean that the 'Indian state', as citizens experience it, takes different forms in different states. Between 1989 and mid-2014, no single party could gain a parliamentary majority. That caused a major decentralization of power away from the once dominant Prime Minister's Office—horizontally to other institutions at the national level, and vertically downward to governments at the state level. Ironically, that decentralization of power at the national level was accompanied by a marked centralization of power in the hands of chief ministers within many states. This is connected to a surge in state and central government revenues after 2003, and to India's far from neoliberal economic order which leaves huge discretionary power in politicians' hands. Various devices—legitimate and illicit—which chief ministers use to increase their influence and to survive in power are examined.